MAPPING THE INTELLECTUAL LANDSCAPE OF VALUE-BASED EDUCATION: A BIBLIOMETRIC ANALYSIS OF RESEARCH TRENDS - Tengku Muda , Tengku Fatimah Muliana; Ismail , Siti Khatijah; Wan Ariffin , Wan Nor Jazmina; Tun Ismail , Wan Nor Azilawanie; Muhamad, Norlia (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This bibliometric analysis investigates the intellectual landscape and research trends in Value-based Education (VbE), a pedagogical paradigm that emphasizes the integration of moral, ethical, and civic values within teaching and learning. Despite its growing global significance, the field remains theoretically fragmented and lacks a comprehensive mapping of scholarly development. Addressing this gap, the present study aims to systematically analyze research output, thematic evolution, and collaborative patterns within VbE scholarship. Using the Scopus database as the primary data source, a total of 611 documents were retrieved through a targeted search strategy that incorporated keywords such as “VbE,” “teaching,” and “learning.” The dataset was refined and standardized using OpenRefine, followed by in-depth visualization and network analysis using VOSviewer software. The analysis reveals that the United Kingdom, the United States, and Australia are the leading contributors in terms of volume and citations. At the same time, countries such as Sweden and Canada demonstrate strong international collaborations. Keyword co-occurrence analysis highlights dominant themes, including ethics, moral education, character development, and decision-making, indicating a multidisciplinary orientation. However, the presence of overlapping and variably defined terms such as “value education” and “values-based education” points to conceptual inconsistencies across studies. The findings also indicate a gradual increase in publications over the past two decades, reflecting a rise in scholarly interest and policy relevance. This study offers critical insights into the structure, scope, and evolution of VbE research, providing a foundational reference for future theoretical consolidation, empirical exploration, and cross-cultural collaboration. It contributes to advancing VbE as a coherent and impactful field of inquiry in the global educational discourse.